A comparison of the functional traits of common reed (Phragmites australis) in northern China: aquatic vs. terrestrial ecotypes. - Liping Li; Wenxuan Han; Niels Thevs; Xiuhong Jia; Chengjun Ji; Dongmei Jin; Ping He; Armin O Schmitt; Giuseppe Tommaso Cirella; Stefan Zerbe (PLoS ONE, 2014)
Common reed (Phragmites australis (Cav.) Trin. ex Steud.) is distributed widely throughout the world with various ecotypes. This research compares the functional traits and biomass allocation patterns of two contrasting reed ecotypes. Twelve pairs of aquatic and terrestrial reed samples were collected in northern China. Significant differences in functional traits between the two reed ecotypes were observed, while biomass allocation patterns of reed organs did not differ significantly except for at the root. The dry matter content (DMC) in the whole of the reed plant, leaf, root, and rhizome was higher; while the specific leaf area (SLA) and specific root length (SRL) were lower in terrestrial versus aquatic reed. The biomass allocation in organs of the two forms of reed was isometric, only root in the terrestrial habitat increased faster with an increase in the whole plant biomass. It can be affirmed that aquatic and terrestrial reed that adapt to different environments generally has distinct leaf and root functional traits but isometric biomass allocation patterns. This suggests different resource acquisition strategies: (1) aquatic reed grows faster with high SLA and SRL and is more responsive to the environment, while (2) terrestrial reed with high DMC grows slower and is less responsive to the adverse environment (e.g. dry soil conditions).